LEGAL ANALYSIS OF LEGAL PROTECTION OF THE RIGHTS OF FOR-WIVES AND CHILDREN AFTER DIVORCE IN INDONESIAN LAWS AND REGULATIONS BASED ON THE VALUES OF JUSTICE - Ade Syafitri; Andoko , Andoko; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
Legal protection for the rights of ex-wives and children after divorce in Indonesia still faces challenges in its implementation. Although regulations such as the Marriage Law and the Compilation of Islamic Law have regulated the obligations of ex-husbands to provide iddah, mut'ah, and children's rights, weak law enforcement mechanisms often result in these rights not being fulfilled. The lack of criminal sanctions for negligent ex-husbands, disparity in treatment in cases of divorce by talak and divorce by lawsuit, and low public legal awareness are the main obstacles in the realization of this legal protection. This study uses a normative legal method with a descriptive-analytical approach to examine legal arrangements and related policy implementation. The results of the study indicate that stricter legal reforms are needed, including enforcing sanctions for ex-husbands who do not fulfill their obligations, implementing an inter-agency interconnection system to ensure the execution of decisions, and increasing women's legal awareness so that they can fight for their rights. With a more comprehensive policy, legal protection for women and children after divorce can be more optimal, creating justice based on the principle of welfare.